Projeto de yoga como extensão universitária - Mauricio, Carine Cassiane Rubira [UNESP]; Pinto, Ana Cláudia Gomes de Amorim [UNESP]; Deutsch, Silvia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Yoga is a practice that involves body, mind and spirit. Once at the university, serves students, faculty, staff and even the local community. This practice benefits are numerous.. Developed with Hatha Yoga, consists of Yoga postures, breathing techniques and meditation which improvements are evident in the physical, emotional and social fields. In addition, the extension project also enables improvement in the research area and the development of future teachers for the workforce.

O Yoga é uma prática que trabalha corpo, mente e espirito. Uma vez inserida na universidade, atende alunos, professores, funcionários e ainda a comunidade local.. Os benefícios desta prática são inúmeros. Desenvolvida na linha da Hatha Yoga, composta por posturas, técnicas de respiração e meditação as melhorias são evidentes nos campos físico, emocional e social. Contudo, o projeto de extensão também possibilita aprimoramento nas pesquisas da área e o desenvolvimento de futuros professores para o mercado de trabalho.
Keywords: Yoga; Extension; Body practice; Yoga; Extensão; Prática corporal